(15b-7)-7(2b+4)=-2

Simple and best practice solution for (15b-7)-7(2b+4)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15b-7)-7(2b+4)=-2 equation:



(15b-7)-7(2b+4)=-2
We move all terms to the left:
(15b-7)-7(2b+4)-(-2)=0
We add all the numbers together, and all the variables
(15b-7)-7(2b+4)+2=0
We multiply parentheses
(15b-7)-14b-28+2=0
We get rid of parentheses
15b-14b-7-28+2=0
We add all the numbers together, and all the variables
b-33=0
We move all terms containing b to the left, all other terms to the right
b=33

See similar equations:

| 7=40/z−1 | | 2/3x-10=16 | | 7=40z−1 | | C+10=-2c-8 | | 4x-13=6x-3 | | 7=40/z | | 3z^2-7z+3=0 | | 10x+13=4x-10 | | n(2)+13=75 | | 6x+6+6x+30=30 | | 9x+2=(3/4)(2x+11) | | -2z=10-z | | 6378.1x=2981.1 | | 11x-86x=22 | | 6378.1x=3981.1 | | 4x-7+x+12=180 | | ((X+1)/2)+((x+5)/3)=5 | | 3/5x=1/7x+16 | | -2n+9=4n-9 | | (X+1)/2+(x+5)/3=5 | | x+12=4x-7 | | x/2x+1=16/40 | | 10k=-7+3k | | 2x+10=18+6x-12 | | 9+3m=-5+5m | | 2/5x=3/10+1/5x | | 4x-12=6x-14 | | 2/5x=3/10x+1/5x | | 7m^2+45m+18=0 | | 7+2(3−8x)=4−6(1+5x) | | 4x4+81=36x | | 2(1+6x)-(x-1)=80 |

Equations solver categories